In silico CDM model sheds light on force transmission in cell from focal adhesions to nucleus. Issue 13 (6th September 2016) - Milan, Jean-Louis; Manifacier, Ian; Beussman, Kevin M.; Han, Sangyoon J.; Sniadecki, Nathan J.; About, Imad; Chabrand, Patrick
Abstract: Cell adhesion is crucial for many types of cell, conditioning differentiation, proliferation, and protein synthesis. As a mechanical process, cell adhesion involves forces exerted by the cytoskeleton and transmitted by focal adhesions to extracellular matrix. These forces constitute signals that infer specific biological responses. Therefore, analyzing mechanotransduction during cell adhesion could lead to a better understanding of the mechanobiology of adherent cells. For instance this may explain how, the shape of adherent stem cells influences their differentiation or how the stiffness of the extracellular matrix affects adhesion strength. To assess the mechanical signals involved in cell adhesion, we computed intracellular forces using the Cytoskeleton Divided Medium model in endothelial cells adherent on micropost arrays of different stiffnesses. For each cell, focal adhesion location and forces measured by micropost deflection were used as an input for the model. The cytoskeleton and the nucleoskeleton were computed as systems of multiple tensile and compressive interactions. At the end of computation, the systems respected mechanical equilibrium while exerting the exact same traction force intensities on focal adhesions as the observed cell. The results indicate that not only the level of adhesion forces, but also the shape of the cell has an influence on intracellular tension and on nucleus strain. The combination of experimental micropost technology with the present CDM model constitutes a tool able to estimate the intracellular forces.